School experiments of the integral education policy and Full Time School: an analysis of the practices carried out in public schools of Belém - PA - Ney Cristina Monteiro de Oliveira; Orlando Nobre Bezerra de Souza; Izete Magno Correa; Cintia Aurora Quaresma Cardoso (Universidade Federal do Norte do Tocantins, 2020)
The wording presents the analysis carried out on the full-time policy implemented in the state education network in Pará from its practical configuration in the reality of 02 (two) elementary schools in the city of Belém-Pa. Reflect on the principles of the instituted policy, management, pedagogical organization and effectiveness in school practices. The theoretical-methodological contribution of this study is based on the qualitative approach of the research, having as procedures the documentary analysis, interviews and application of questionnaires to understand each phase of the implantation, the perception of managers and teachers, as well as to analyze the initiatives carried out, the challenges faced, the difficulties and the possibilities of pedagogical innovation. It was concluded that the policy did not have the official support due, leaving the educators in charge of its effective implementation. Despite small advances, the lack of material conditions for the development of school practices that qualified the offer of full time for the integral training of students prevailed.